Systematic bias between running speed and metabolic power data in elite soccer players: Influence of drill type - Gaudino, P.; Iaia, F. M.; Alberti, G.; Hawkins, R. D.; Strudwick, A. J.; Gregson, W. (International Journal of Sports Medicine, 2014)
The aims of the present study were to: i) evaluate the agreement between estimates of high-intensity activity during soccer small-sided games (SSGs) based on running speed alone and estimated metabolic power derived from a combination of running speed and acceleration; ii) evaluate whether any bias between the 2 approaches is dependent upon playing position or drill characteristics. 3 types of SSGs (5vs5, 7vs7 and 10vs10) were completed by 26 English Premier League outfield players. A total of 420 individual drill observations were collected over the in-season period using portable global positioning system technology. High-intensity activity was estimated using the total distance covered at speeds>14.4 km · h-1 (TS) and the equivalent metabolic power threshold of > 20 W · kg-1 (TP). We selected 0.2 as the minimally important standardised difference between methods. High-intensity demands were systematically higher (~100%, p<0.001) when expressed as TP vs. TS irrespective of playing position and SSG. The magnitude of this difference increased as the size of SSG decreased (p<0.01) with a difference of ~200% observed in the 5vs5 SSG. A greater difference between TP and TS was also evident in central defenders compared to other positions (p<0.05) particularly during the 5vs5 SSG (~350%). We conclude that the high-intensity demands of SSGs in elite soccer players are systematically underestimated by running speed alone particularly during "small" SSGs and especially for central defenders. Estimations of metabolic power provide a more valid estimation as to the true demands of SSGs.